Auditoría de Gestión a la Empresa de Servicio Aéreo Regional de la ciudad de Macas, provincia de morona Santiago, período 2014, para determinar a la eficiencia, eficacia y efectividad. - Morocho Plasencia, Lilian Patricia (2015)
This research work has as its theme AUDIT MANAGEMENT COMPANY REGIONAL AIR SERVICE the city of Macas, Morona Santiago province, PERIOD 2014 to determine the efficiency, effectiveness and efficiency. It is oriented to conduct a performance audit where administrative efficiency and its influence on the achievement of goals, company goals are determined. The project consists of five chapters that allowed them to finish the analysis and helped publicize the results and are structured as follows: CHAPTER I, in this chapter is detailed Referencial. - Framework consists of approach and formulation of the problem, the general, specific and justified objectives which are being pursued by the research work. CHAPTER II, Marco Teórico. - supports the scientific content of the research and the basic conceptualizations of research variables such as audit and administrative efficiency. CHAPTER III, Marco Metodológico. - relates to methods and research designs, type of research, techniques and data collection instruments used in the research process to achieve and learn through the deficiencies of the results. CHAPTER IV, the findings with their findings and recommendations and finally analysis of the results thereof to assist in decision-making to managers of the company are detailed.